2022
DOI: 10.3389/fvets.2022.986269
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin-1, GATA-3, and Ki67 expressions and their correlation with pathological findings in canine bladder urothelial carcinoma

Abstract: The bladder urothelial carcinoma (UC) represents ~2% of malignant neoplasms in dogs and is a therapeutic challenge in veterinary medicine. Although it is considered the most common bladder cancer in dogs, few previous studies have investigated different markers that correlate with clinical and pathological parameters. Therefore, this study aimed to evaluate Caveolin-1, GATA-3, and Ki67 immunostaining in canine UC samples to evaluate their correlations with histopathological variables. Thirty tumor samples were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…A recent study reported a weak and positive correlation between the expression of GATA-3 and greater mitotic activity in bladder cancer in dogs. This result suggested that increased GATA-3 expression indicated a worse prognosis for this tumor; however, those authors considered that the stage of tumor progression in the sample set studied was exceptionally homogeneous and emphasized that the biological role of GATA-3 in bladder urothelial carcinoma is still poorly understood ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study reported a weak and positive correlation between the expression of GATA-3 and greater mitotic activity in bladder cancer in dogs. This result suggested that increased GATA-3 expression indicated a worse prognosis for this tumor; however, those authors considered that the stage of tumor progression in the sample set studied was exceptionally homogeneous and emphasized that the biological role of GATA-3 in bladder urothelial carcinoma is still poorly understood ( 21 ).…”
Section: Introductionmentioning
confidence: 99%